Single cell analyses reveal specific distribution of anti‐bacterial molecule Perforin‐2 in human skin and its modulation by wounding and Staphylococcus aureus infection. Issue 3 (12th February 2019) - Strbo, Natasa; Pastar, Irena; Romero, Laura; Chen, Vivien; Vujanac, Milos; Sawaya, Andrew P.; Jozic, Ivan; Ferreira, Andrea D. F.; Wong, Lulu L.; Head, Cheyanne; Stojadinovic, Olivera; Garcia, Denisse; et al.
Abstract: Perforin‐2 (P‐2) is a recently described antimicrobial protein with unique properties to kill intracellular bacteria. We investigated P‐2 expression pattern and cellular distribution in human skin and its importance in restoration of barrier function during wound healing process and infection with the common wound pathogen Staphylococcus aureus . We describe a novel approach for the measurement of P‐2 mRNA within individual skin cells using an amplified fluorescence in situ hybridization (FISH) technique. The unique aspect of this approach is simultaneous detection of P‐2 mRNA in combination with immune‐phenotyping for cell surface proteins using fluorochrome‐conjugated antibodies. We detected P‐2 transcript in both hematopoietic (CD45 + ) and non‐hematopoietic (CD45 − ) cutaneous cell populations, confirming the P‐2 expression in both professional and non‐professional phagocytes. Furthermore, we found an induction of P‐2 during wound healing. P‐2 overexpression resulted in a reduction of intracellular S. aureus, while infection of human wounds by this pathogen resulted in P‐2 suppression, revealing a novel mechanism by which S. aureus may escape cutaneous immunity to cause persistent wound infections.